2012
DOI: 10.1007/s10552-012-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends in head and neck cancers and human papillomavirus (HPV)-associated oropharyngeal cancer in Canada, 1992–2009

Abstract: The incidence patterns of HPV-associated oropharyngeal cancer and head and neck cancer overall show contrasting trends. Findings highlight the need to surveil HPV-associated oropharyngeal cancer separately from other cancers of the head and neck region in order to monitor these emerging trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 30 publications
3
53
1
Order By: Relevance
“…17 We observed that the increase in incidence of oropharyngeal cancer among men was twice that among women (annual percentage change 3.4 v. 1.5) between 1975 and 2009. Similarly, both Canadian 16 and US 18 data show that the increased incidence of HPV-associated head and neck cancers was greater among men, most notably the younger groups. In 2 previously reported Canadian studies, 16,17 ethnic minorities appeared to be at higher risk than the general population of both oropharyngeal cancer and oral cavity cancers.…”
Section: Cmaj Openmentioning
confidence: 88%
See 2 more Smart Citations
“…17 We observed that the increase in incidence of oropharyngeal cancer among men was twice that among women (annual percentage change 3.4 v. 1.5) between 1975 and 2009. Similarly, both Canadian 16 and US 18 data show that the increased incidence of HPV-associated head and neck cancers was greater among men, most notably the younger groups. In 2 previously reported Canadian studies, 16,17 ethnic minorities appeared to be at higher risk than the general population of both oropharyngeal cancer and oral cavity cancers.…”
Section: Cmaj Openmentioning
confidence: 88%
“…Similarly, both Canadian 16 and US 18 data show that the increased incidence of HPV-associated head and neck cancers was greater among men, most notably the younger groups. In 2 previously reported Canadian studies, 16,17 ethnic minorities appeared to be at higher risk than the general population of both oropharyngeal cancer and oral cavity cancers. In the US, non-Hispanic white and Hispanic populations experienced greater increases in the incidence of HPV-associated head and neck cancers than other groups.…”
Section: Cmaj Openmentioning
confidence: 88%
See 1 more Smart Citation
“…Global incidence rates of oropharyngeal cancer (OPC) are rising, particularly in economically developed countries such as Canada, United States, Japan, Switzerland, Australia, England and parts of Eastern Europe [3][4][5][6][7]. Rates of oral cavity cancer (OCC) are also rising among men and women in some European countries, stabilising in certain Asian countries and decreasing in Canada and USA [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the increase in oropharyngeal cancer in Canada has been reported using Canadian national cancer registry data 12,13 , population-based studies allow only for inferences about the influence of hpv on changes in incidence. Centres across Canada have now begun routine testing of head-and-neck cancers for hpv, but the paper by Nichols and colleagues provides case-by-case information about the contribution of hpv to the dramatic increase in the oropharyngeal cancer incidence seen in Canada since the early 1990s.…”
mentioning
confidence: 99%